Migrations of North Caucasians to the Ottoman Empire: initial stage (1858-1862) - Georgy V. Chochiev (Кавказология, 2024)
The article traces the process of formation of a stable and massive migration flow of representatives of the peoples of the North Caucasus to the Ottoman Empire in the period from the end of 1858 to the middle of 1862, conditionally identified as the initial stage of the Caucasian muhajirism. Involvement of a significant range of published Russian and predominantly unpublished Turkish and British archival documents along with modern domestic and foreign historiography allows us to expand and clarify our knowledge on the socio-economic, internal and external reasons and accompanying circumstances of the said resettlement, its dynamics and evolution, quantitative and ethnic parameters, as well as the approaches and steps in this sphere of official St. Petersburg and Istanbul. While recognizing the unified, pan-Caucasian nature of this socio-migrational phenomenon, attention is drawn to certain specificities in its nature, intensity and scale in different parts of the region.